Media Framing on the Hamas-Israel Conflict: An Analysis of Kompas.com and CNBC Indonesia News in October 2023 - Septiani, Pika; Widiastuti, Wahyu; Makhrian, Andy (GoAcademica Research & Publishing, 2024)
International conflict is a social phenomenon in international law, involving subjects that seek to harm other states. Causes are varied, including disputes over material factors such as territorial sea conflicts and economic competition. Conflicts often stem from differences in ethnic interests, such as those between Palestine and Israel. The media plays a role in shaping public opinion, news coverage of the Palestinian-Israeli conflict can be influenced by partisanship, news framing, and geopolitical influences. The mass media, such as kompas.com and CNBC Indonesia, portray the Israeli-Palestinian conflict through news framing that influences readers' perceptions. Kompas.com tends to emphasize Israel's declaration of war on Hamas and the casualties of the attacks, giving emphasis to Israel's actions in response to the attacks and creating sympathy for Israel. They also highlighted Hamas' exploitation of the geopolitical gap in the Middle East. On the other hand, CNBC Indonesia was more neutral in reporting on the conflict, not emphasizing one side over the other. They include Russia's view of the conflict, providing additional viewpoints and showing that there are other countries influencing or providing perspectives on the conflict. With qualitative research methods and framing analysis William A. Gamson and Andre Modigliani, this research revealed that kompas.com highlighted PM Netanyahu's statement that Isr.